OTOMASI IRIGASI JANGGELAN BERBASIS INTERNET OF THINGS - Angga Prasetyo; Arief Rahman Yusuf; Yovi Litanianda (MULTITEK INDONESIA, 2020)
Internet and industrial revolution 4.0 brought influence in society, especially in agriculture, the changes that occurred were in farming activities by applying appropriate technology. This activity is much in demand, especially the planting irrigation process. However, the process of irrigation or irrigation that has used appropriate technology still has some shortcomings such as pumping and control hardware systems that are still stand-alone using a timer, so the automation and monitoring process is still semi-manual. As done in the cultivation of janggelan (black grass jelly), which focuses more on irrigation governance, because the janggelan requires water intake and fertilizer nutrition which is always monitored. In order for the device to function optimally, it is made a miniature tool based on the internet of things to facilitate control and monitoring via a smartphone. In order for the miniature tool can be integrated and function in real-time with the Internet of things, then all devices (YL 69 sensors, Relay, Board NodeMCU esp 8266 are given C language coding commands, via the Arduino ID interface. synchronization between the user interface, the miniature devices, and Internet networks running normally. IoT devices and internet networks can run normally. Sensor data is able to give the pump selenoid command to turn on under humidity conditions of less than 65%, while the pump is off at 40% humidity. The success rate of data sent on Google Firebase with an average total ping of 70.28% was all successful.